Strength and Balance Improvement with Plank Exercise Variations - Miftachul Amiruddin; Oce Wiriawan; Muhammad Muhammad (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2023)
This study aims to determine the effect of core stability exercises (Elbow Plank, High Plank, and Elbow Plank With Legs Open) on abdominal muscle strength and balance.  Quasi-experimental research and research design using nonequivalent control group design. The purposive sampling technique was used in this study to determine the research subjects where the total research subjects obtained 32 people. The research instruments used were the sit up test (30 seconds) to measure abdominal muscle strength and the standing stork test to measure balance. The results of the manova test showed that there was a significant difference, while the post hoc test showed that the results did not have a significant difference in influencing abdominal muscle strength and balance. The results of plank training showed a significant difference, both in abdominal muscle strength and balance. The conclusion of this study is that the plank core stability variation training method has a more significant effect on increasing abdominal muscle strength and balance.